The Effect of E-Filling Application and Tax Knowledge on Taxpayer Satisfaction (Case Study at PT Sumatra Palm Raya) - Sunita, Destiny; Wahyuni, Putri; Wulandari, Tri (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2023)
This study aims to determine whether E-Filling and Taxation Knowledge have a significant effect on Taxpayer Satisfaction (Case Study at PT Sumatra Palm Raya). This research uses quantitative data methods and data sources come from primary data. The population in this study is all employees working at PT Sumatra Palm Raya as many as 36 employees. The sample in this study was permanent employees who had NPWP who worked at PT Sumatra Palm Raya totaling 30 respondents using purposive sampling data collection techniques. Data analysis and testing consists of validity tests, reliability tests, descriptive statistics, classical assumption tests, multiple linear regression analysis, partial (t tests) and simultaneous hypothesis tests (F tests), and determination coefficient tests. The results of this study show that the Application of E-Filling has a significant partial effect on Taxpayer Satisfaction with a calculated t value of 2,144 > T table 2,048. Taxation Knowledge has no effect and is not significant on Taxpayer Satisfaction with a calculated t value of 1.963 < T table 2.048. The application of E-Filling and Taxation Knowledge have a significant effect simultaneously on Taxpayer Satisfaction with a calculated F value of 8.772 > an F table value of 3.35 and a regression coefficient value of 34.9%.